Assessment of sub-centres of Belagavi district according to Indian public health standards 2012 guidelines: a cross sectional study - Patil, Shrinivas K.; M. S., Shivaswamy (International Journal Of Community Medicine And Public Health, 2017)
Background: In the public sector, a sub-health centre (sub-centre) is the most peripheral and first point of contact between the primary health care system and the community. The current level of functioning of the Sub-centres is much below the expectations. Objective: To assess sub-centres of Belagavi District according to Indian public health standards 2012 guidelines. Methods: A facility based cross-sectional study was conducted in Belagavi district of Karnataka. forty SCs, four SC from each of the 10 Talukas of Belagavi district were selected by simple random sampling. Study period: 1st January to 31st December 2014. Data collected - using a predesigned and structured questionnaire for IPHS facility survey. Results: The study showed 35% of SCs were catering the services for population as per the norms. Services like ante-natal clinics, post-natal clinics and immunization sessions were conducted regularly in all the SCs. About 33% of SCs had no buildings. A deficiency worth highlighting in the present study was the absence of residential facilities for the staff in half of the SCs. Proper supervision and monitoring of the service delivery activities of the SC staff was done only in 70% of SCs. Conclusions: IPHS guidelines are not being followed at SC level in the district. Recruitment of SC staff especially the Health Worker Male post should be filled at all the SCs for efficient functioning of the SCs. The SC should be periodically surveyed to identify the deficiency and necessary action could be taken to correct it.